PELATIHAN KESELAMATAN TERHADAP GEMPA DI KELURAHAN BENDUNG KECAMATAN KASEMEN KOTA SERANG - Suradjin Sutjipto; Indrawati Sumeru; Bambang Endro Yuwono; Khotijah Lahji; Divo Trinugtaha Putra (Indonesian Collaboration Journal of Community Services, 2023)
Indonesia is an earthquake-prone country. Almost all of the islands in Indonesia lie in the ring of fire of the world's earthquakes. Earthquake disasters often occur and cause a lot of loss, both property and casualties. However, until now, education for the public to be prepared for earthquake disasters is still inadequate. The community is always unprepared and only resigned to fate in facing the earthquake. Earthquake disaster mitigation is generally the responsibility of the government, but the government itself cannot make effective efforts without the help of experts and the participation of the community itself. The PKM Earthquake Safety Training Program is aimed at the people of Kelurahan Bendung, Kecamatan Kasemen, Serang, Banten because based on the findings of the latest earthquake fault, namely the Baribis Fault, the area has the potential for a large earthquake to occur. This program aims to educate the people there about prevention efforts before an earthquake occurs, what to do when an earthquake occurs, and what to do after an earthquake occurs. It is hoped that the knowledge provided will be useful, and the people there can be prepared for earthquake disasters, so that loss of life and property due to the earthquake can be diminished.